A European Study of the Performance and Safety of MINIject in Patients With Medically Uncontrolled Open-angle Glaucoma (STAR-II). Issue 10 (October 2020) - García Feijoó, Julián; Denis, Philippe; Hirneiß, Christoph; Aptel, Florent; Perucho González, Lucía; Hussain, Zubair; Lorenz, Katrin; Pfeiffer, Norbert
Abstract : Precis: In this European study (STAR-II), MINIject, a novel, ab-interno, supraciliary minimally invasive glaucoma surgery device, effectively lowered intraocular pressure (IOP) and the need for IOP-lowering medications in patients with primary open-angle glaucoma. Purpose: This study evaluates the safety and performance of a minimally invasive supraciliary glaucoma drainage device (MINIject DO627) for surgical treatment of primary open-angle glaucoma in patients refractory to topical hypotensive medications. Methods: In a prospective, interventional, single-arm, multicenter, European study (STAR-II), MINIject was successfully implanted in a stand-alone procedure in 29 of 31 patients in 8 sites in 3 countries. The primary endpoint was the success rate 6 months after surgery >60% (defined as diurnal IOP ⩽21 and >5 mm Hg with ≥20% IOP reduction from baseline, with/without glaucoma hypotensive medication). ClinicalTrials.gov: NCT03624361. Results: At the 6-month follow-up, the primary endpoint was fulfilled, with 75.9% of patients reaching prospectively defined success. The mean IOP was reduced by 40.2% (9.9 mm Hg) to 14.7±6.0 mm Hg at 6 months from 24.6±3.8 mm Hg at baseline. The use of IOP-lowering medication ingredients was reduced by 63.4% from 2.9±1.2 at baseline to 1.0±1.3. Furthermore, 79.3% of the patients had mean IOP ⩽18 mm Hg, 82.8% achieved a ≥20% IOP reduction, and 55.2% were medication free at 6 months. Six device-related serious adverse events were reported in the study eye: IOP increase (3/31 patients, 9.7%), and single reports of eye pain, corneal erosion, and chorioretinal folds (1/31, 3.2%), all of which resolved. There was minimal change to corneal endothelial cell density. Conclusion: Ab-interno supraciliary surgical implantation using MINIject DO627 in a stand-alone procedure significantly lowers IOP by 40% at the 6-month follow-up, while reducing the need for IOP-lowering medication.